The undercurrents of neoliberal ethics in science curricula: a critical appraisal. Issue 1 (2nd January 2021) - Sharma, Ajay; Alvey, Elaine Margaret
ABSTRACT: The world is confronted with wicked environmental problems that cannot be well understood or acted upon without addressing their ethical dimensions. Research shows that official science curricula on environmental science and ecology topics are shaped by the scientific discourse and environmental discourses of ecological modernization and green governmentality . These discourses carry tacit ethical stances that need to be acknowledged and assessed for their suitability in helping us understand and tackle wicked environmental problems. This paper explores the ethical alignments of ecology and environmental science related science content standards in the United States. Our analysis suggests that the intended science curricula in this country appears to support an embedded ethical stance marked by neoliberal utilitarianism and virtue ethics. Further, we highlight the possibility that neoliberal ethical orientations run the risk of frustrating students' hopes for a sustainable and socioecologically just world.